ASPEK-ASPEK PSIKOLOGIS DALAM PEMBELAJARAN - Erita, Selvia (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri (IAIN) Kerinci, 2016)
An educator should be able to realize the teaching behavior appropriately, in order to be able to realize the fair behavior of students through effective teaching and learning interactions in a conducive teaching and learning situation. One of them know what the psychological aspects in teaching. Psychological aspects of learning including the interests, attitudes, motivation and activity arising or developing in the learning process. Mathematics learning objectives related to their interests, attitudes, motivation, creativity and activity can be acceptable if the learning activity contributes to the development of the individual, social competence, or life satisfaction.